Synthesis, properties, and optical applications of low-dimensional perovskites - Zhang, Yupeng; Liu, Jingying; Wang, Ziyu; Xue, Yunzhou; Ou, Qingdong; Polavarapu, Lakshminarayana; Zheng, Jialu; Qi, Xiang; Bao, Qiaoliang (Chemical communications (Cambridge, England), 2016)
Metal-halide perovskites have been hailed as remarkable materials for photovoltaic devices and, recently, their star has also been on the rise in optoelectronics and photonics. In particular, the optical properties of a metal-halide perovskite can be widely manipulated once its bulk structure has been reduced to a low-dimensional structure, allowing multiple functionalities of light generation, emission, transmission, and detection to be realized in one material. In this paper, we highlight the recent advances in the synthesis of low-dimensional metal-halide perovskites and their unique properties as well as their novel optoelectronic and photonic applications. It is anticipated that this review can serve as an overview and evaluation of state-of-the-art synthesis techniques as well as nanoscale optoelectronics and photonics based on low-dimensional perovskite nanocrystals. This feature article provides an overview of synthesis, properties and applications of low-dimensional perovskites.